2022
DOI: 10.1177/00302228211065275
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement among Adolescents with Intellectual Disability: A Qualitative Study

Abstract: The current study was conducted to explore the bereavement (experienced loss of a loved one through death within time frame of 0–3 years span). Seven adolescents (10–19 years old) with intellectual disability were included in the study. Semi-structured interviews were conducted through interview guide which was prepared with the help of Piaget’s theory of cognitive development concept related to death. Data was analyzed with content analysis and six major themes were derived, that is, meaning of death, death r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Where reported (10/17, 59%), duration of the interviews ranged from 15 to 90 min (Cithambaram et al, 2020; Cithambarm et al, 2021; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; McKenzie et al, 2017; Rodríguez Herrero et al, 2015; Ryan et al, 2012; Thorp et al, 2018; Voss et al, 2020). Only two studies reported interviews taking place over multiple days (Haider & Zaman, 2022; McRitchie et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where reported (10/17, 59%), duration of the interviews ranged from 15 to 90 min (Cithambaram et al, 2020; Cithambarm et al, 2021; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; McKenzie et al, 2017; Rodríguez Herrero et al, 2015; Ryan et al, 2012; Thorp et al, 2018; Voss et al, 2020). Only two studies reported interviews taking place over multiple days (Haider & Zaman, 2022; McRitchie et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Where reported (10/17, 59%), duration of the interviews ranged from 15 to 90 min (Cithambaram et al, 2020; Cithambarm et al, 2021; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; McKenzie et al, 2017; Rodríguez Herrero et al, 2015; Ryan et al, 2012; Thorp et al, 2018; Voss et al, 2020). Only two studies reported interviews taking place over multiple days (Haider & Zaman, 2022; McRitchie et al, 2014). Settings of data collection was reported in eight of the 16 publications (50%) (Butler et al, 2012; Haider & Zaman, 2022; McEvoy et al, 2012; McEvoy et al, 2017; Rodríguez Herrero et al, 2015; Ryan et al, 2012; Thorp et al, 2018; Voss et al, 2020) When specified, the settings of data collection were characterised as being “comfortable” (Thorp et al, 2018) or “quiet” (McEvoy et al, 2012; McEvoy et al, 2017; Rodríguez Herrero et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because teens with ID demonstrate variation in adaptive and cognitive abilities, proxy reporting by utilizing the measurement tools with the surviving parent/guardian or caregiver of the teen could alternatively be used, even at the risk of secondary reporting not fully capturing the experiences of the teens. In the limited prior research on teens with ID and their grief experiences, one study interviewed teens with ID directly (Haider & Zaman, 2022), but the two other published studies on children with ID have worked with professionals such as teachers or psychologists (Ducy & Stough, 2018; McClean & Guerin, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Varying levels of support may be needed for individuals with ID in navigating daily functioning and novel situations, and in understanding and incorporating new or complex information and skills (Gjertsen, 2019; Maulik et al, 2011). Given the additional physical and emotional transitions from adolescence to young adulthood, and developing cognitive maturity, teens with ID may have particular vulnerability in relation to significant life changes (Haider & Zaman, 2022).…”
mentioning
confidence: 99%